ESTIMATION OF THE STABILITY OF TRAITS INDUCED BY TRITON X-100 IN COMMON WHEAT (TRITICUM AESTIVUM L.) - K. Kh. Makhmudova; E. D. Bogdanova; S. S. Kirikovich; E. V. Levites (Вавиловский журнал генетики и селекции)
Studies of several generations of common wheat lines carrying changes induced by nonionic detergent Triton X-100 (TX-100) are reported. It is shown that the induced changes recorded in the first generations are also observed in the fourth, fifth and sixth generations.